Analyzing the Impact of Internet Banking on Profitability in the Indonesian Banking Sector - Sukmamuliawanty, Elza; Umayaksa, Fitra Amalya; Leon, Farah Margaretha (International Journal of Social Science and Business, 2024)
This research aims to identify variables that influence profitability in banking companies listed on the Indonesian Stock Exchange. The addition of the bank capital variable as an independent variable is a novel part of this research. This research method involves collecting data from 20 banking companies over a six-year period (2018–2023) with a total of 120 data that meet the criteria by applying data processing analysis using panel data regression analysis techniques. The research results found that internet banking had a significant positive impact on return on assets, while operational performance and credit risk had a significant positive impact on bank performance. Bank capital also has a significant negative effect on return on equity. Apart from that, spread and intermediation costs have no effect on bank performance. The implication for financial managers is to provide guidance for financial managers to optimize the use of operational performance, paying attention to credit risk to increase bank profitability. Financial managers also need to be proactive in developing strategies, facing challenges, and adapting to technological developments in utilizing internet banking to ensure the bank's success in the digital era. Then investors need to consider the potential profits and risks associated with credit risk because it can disrupt performance in the banking sector, as well as carry out fundamental analysis and portfolio diversification to minimize risk. Investors also need to look at bank operations by paying attention to improving bank operational performance because this can increase bank income from various types of services, such as transaction fees, deposit interest and loan fees.